The snows of Jaspre - Caraker, Mary (Boston : Houghton Mifflin, 1989)
Morgan Farraday, an administrator from Earth, becomes involved in the destiny of the planet Jaspre when her daughter Dee meets the charismatic Anders Ahlwen, whose followers receive psychic powers and a transcendent spiritual reality from the artificial sun Argus.
Keywords: Science fiction